Scientific Approach-Based Student Worksheet to Improve Elementary School Student's Scientific Process Skill - Kartika, Leli; Distrik, I Wayan; Pujiati, Pujiati (Indonesian Journal of Science and Mathematics Education, 2022)
This research and development aim to produce student worksheets based on a valid, practical, and effective scientific approach to improve the science process skills of fifth-grade students in elementary schools. The development procedure adopted the Borg and Gall Model, which was simplified into seven steps. In the main field test phase, the research sample was 20 fifth-grade students at SDN 5 Kresnomulyo. This study uses a one-group pretest-posttest design. Data analysis used paired sample t-test to test the difference between the pretest and posttest. The results showed that student worksheets based on the scientific approach were declared valid with content validity values of 86.63 and construct validity of 85.63, practical as indicated by positive student responses, and effective as indicated by n-gain values paired sample t-test results. It can be concluded that the developed student worksheets are feasible to use and can improve students' science process skills.